Our first 'social media election': Online battle: It has increased tempo of political debate - Tan, Choe Choe (New Sunday Times, 2013)
IT is clear from any account that both the coalitions, Barisan Nasional (BN) and Pakatan, have gone all out in trying to engage and interact with the people online. In February, Prime Minister Datuk Seri Najib Razak himself described this general election as Malaysia's first "social media election" as politicians from both sides of the divide had gone online to communicate with the people.